Stochastically Forced Compressible Fluid Flows : Navier-Stokes Equations with Stochastic Driving Forces. - Breit, Dominic (De Gruyter series in applied and numerical mathematics., 2018)
The series is devoted to the publication of high-level monographs and specialized graduate texts which cover the whole spectrum of applied mathematics, including its numerical aspects. The focus of the series is on the interplay between mathematical and numerical analysis, and also on its applications to mathematical models in the physical and life sciences.